Dissolved gas analysis in transformer oil using Ni-Doped GaN monolayer: A DFT study - Wang, Jincong; Zhang, Xiaoxing; Liu, Li; Wang, Zengting (Superlattices and microstructures, 2021)
In order to evaluate the running status of the transformer, through the detection of the dissolved gas in oil using highly sensitive gas sensor is proposed as an effective method. In this work, the adsorption characteristics of dissolved gases (H2, C2H2, CH4) in transformer oil on Ni-doped GaN (Ni-GaN) were analyzed based on density functional theory, and the potential of the Ni-GaN as a gas sensor was explored. The results show that the Ni-GaN has the largest adsorption energy to C2H2. On the other hand, the Ni-GaN has outstanding response to H2, C2H2 and CH4, and its response are 6.88 × 103, 6.57, 39.38, respectively. According to the analysis of frontier molecular orbital theory, the band gap of the Ni-GaN will increase after adsorption of three kinds of gases. This also confirms the sensing behavior of the Ni-GaN to three kinds of gases. In addition, the Ni-GaN has excellent desorption behavior for CH4. When the temperature is 398 K, the recovery time is only 8.90 s. Based on the working mechanism of the field effect transistor, by adjusting the strength of the applied electric field, it is found that the charge transfer in the adsorption process can be effectively adjusted. This work provides theoretical guidance for the development of the Ni-GaN gas sensitive sensor for detecting dissolved gas in transformer oil. [Display omitted] •The most stable site for Ni doping onto the GaN monolayer is analyzed.•The interaction mechanism of the dissolved gas in oil (H2, C2H2, CH4) on the Ni-GaN surface is studied.•We have explored the potential of the Ni-GaN as a resistive sensor and a field effect transistor sensor.